Karya Tari “Nan Bagandiang” Representasi Prosesi Manjopuik Limau Masyarakat Lubuk Jambi, Kabupaten Kuantan Singingi, Provinsi Riau - Jenilva Magrilla; Yan Stevenson; Dony Osmond; Ariefin Alham Jaya Putra (INDO PUBLISHING, 2026)
The Manjopuik Limau Tradition or Menjemput Limau is a tradition carried out by the Community in the Lubuk Jambi Region, Kuantan Mudik District, Kuantan Singingi Regency, Riau Province. This tradition is a tradition for Maagiah Tando (giving a sign) to a girl carried out by a young man with the aim of conveying the intention of establishing a relationship with the girl. In this work, Nan Bagandiang will raise the tradition of manjopuik limau as a source of inspiration for the work. This work raises three important stages in the traditional procession, namely the delivery process, the delivery of petitah-petitih, and the procession of the procession on the banks of Batang Kuantan. This tradition is interpreted as a symbol of the sincerity of a young man in establishing a relationship with a girl towards married life. Through the development of movements based on Randai Kuantan Ali Baba, this work presents a form of group choreography that emphasizes the values of togetherness, respect for customs, and the relationship between humans and traditions that are passed down from generation to generation. Nan Bagandiang was performed at the Hoeridjah Adam performance hall with eighteen dancers. It is hoped that this dance will contribute to the preservation of regional culture, particularly that of Lubuk Jambi, Kuantan Singingi Regency